1983
DOI: 10.1126/science.222.4630.1283
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Winter: Global Consequences of Multiple Nuclear Explosions

Abstract: The potential global atmospheric and climatic consequences of nuclear war are investigated using models previously developed to study the effects of volcanic eruptions. Although the results are necessarily imprecise due to wide range of possible scenaros and uncertainty in physical parameters, the most probable first-order effects are serious. Significant hemispherical attenuation of the solar radiation flux and subfreezing land temperatures may be caused by fine dust raised in high-yield nuclear surface burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
292
3
5

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 712 publications
(306 citation statements)
references
References 59 publications
6
292
3
5
Order By: Relevance
“…These particles are assumed to be immediately lifted by the fires to the upper troposphere/lower stratosphere region where they will reflect and absorb solar radiation, locally heating the atmosphere and cooling the surface. The first studies using global climate models (GCMs) to examine the impact of the particles [e.g., Turco et al, 1983] showed catastrophic climatic consequences of a nuclear war between superpowers, with subfreezing land temperatures even during summer. More recent studies, using state-of-the-art GCMs, have assessed the damage that might result from a more restrictive use of nuclear weapons [Robock et al, 2007;Toon et al, 2007aToon et al, , 2007bMills et al, 2008;Stenke et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…These particles are assumed to be immediately lifted by the fires to the upper troposphere/lower stratosphere region where they will reflect and absorb solar radiation, locally heating the atmosphere and cooling the surface. The first studies using global climate models (GCMs) to examine the impact of the particles [e.g., Turco et al, 1983] showed catastrophic climatic consequences of a nuclear war between superpowers, with subfreezing land temperatures even during summer. More recent studies, using state-of-the-art GCMs, have assessed the damage that might result from a more restrictive use of nuclear weapons [Robock et al, 2007;Toon et al, 2007aToon et al, , 2007bMills et al, 2008;Stenke et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of nuclear winter was reviewed by a committee of the National Research Council (NRC, 1985). In general, the case put forward by Turco et al (1983Turco et al ( , 1984 was supported with the strong recommendation that the uncertainties be reduced by further research directed toward achieving an understanding of the basic processes that are important to the problem.…”
Section: Introductionmentioning
confidence: 88%
“…The concept of "nuclear winter" has been posutlated with a number of assumptions regarding the smoke produced by postnuclear-exchange fires (Turco et al, 1983(Turco et al, , 1984. The general premise is: after the use of nuclear weapons, sufficient smoke would be generated from fires and deposited in the atmosphere to cause a decrease in the incident solar energy reaching the Earth's surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations